Transferability and additivity of dihedral parameters in polarizable and nonpolarizable empirical force fields - Zgarbová, Marie; Rosnik, Andreana M; Luque, F Javier; Curutchet, Carles; Jurečka, Petr (Journal of computational chemistry, 2015)
Recent advances in polarizable force fields have revealed that major reparameterization is necessary when the polarization energy is treated explicitly. This study is focused on the torsional parameters, which are crucial for the accurate description of conformational equilibria in biomolecules. In particular, attention is paid to the influence of polarization on the (i) transferability of dihedral terms between molecules, (ii) transferability between different environments, and (iii) additivity of dihedral energies. To this end, three polarizable force fields based on the induced point dipole model designed for use in AMBER are tested, including two recent ff02 reparameterizations. Attention is paid to the contributions due to short range interactions (1-2, 1-3, and 1-4) within the four atoms defining the dihedral angle. The results show that when short range 1-2 and 1-3 polarization interactions are omitted, as for instance in ff02, the 1-4 polarization contribution is rather small and unlikely to improve the description of the torsional energy. Conversely, when screened 1-2 and 1-3 interactions are included, the polarization contribution is sizeable and shows potential to improve the transferability of parameters between different molecules and environments as well as the additivity of dihedral terms. However, to reproduce intramolecular polarization effects accurately, further fine-tuning of the short range damping of polarization is necessary.
Keywords: Quantum Theory; voda; Water; Molecular Conformation; ethylendichloridy; Thermodynamics; molekulární modely; kvantová teorie; halogenace; rozpouštědla; Solvents; Ethylene Dichlorides; statická elektřina; Halogenation; Models, Molecular; termodynamika; molekulární konformace; Static Electricity